2020
DOI: 10.1002/rnc.4852
|View full text |Cite
|
Sign up to set email alerts
|

Consensus control of output‐constrained multiagent systems with unknown control directions under a directed graph

Abstract: Summary This paper presents a novel distributed adaptive control algorithm for uncertain higher‐order nonlinear multiagent systems subject to output constraints and unknown control directions. Regarding the latter, a generic class of cases is considered, allowing completely unknown and even nonidentical control directions. Furthermore, the communication topology is only required to contain a fixed directed spanning tree. To guarantee the output constraints and address the asymmetric directed communication topo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Note that the proposed CFDL-DAC can be extended to deal with the leaderless control problems [34], [35] since it is applicable as long as the local measurement information can be described, which is demonstrated by (3). However, the results in [34], [35] are obtained for continues-time multiagent systems with unknown control directions, and this paper considers discrete-time multi-agent systems where the control directions are known. Therefore, the two obstacles are required to be tackled before utilizing the proposed approach.…”
Section: B Distributed Control Gain Updating Algorithmmentioning
confidence: 99%
“…Note that the proposed CFDL-DAC can be extended to deal with the leaderless control problems [34], [35] since it is applicable as long as the local measurement information can be described, which is demonstrated by (3). However, the results in [34], [35] are obtained for continues-time multiagent systems with unknown control directions, and this paper considers discrete-time multi-agent systems where the control directions are known. Therefore, the two obstacles are required to be tackled before utilizing the proposed approach.…”
Section: B Distributed Control Gain Updating Algorithmmentioning
confidence: 99%
“…. , 2(n − 1) + 1},L is the related Laplacian matrix, and the edge setĒ can be deduced from (16). Since rank(c 1 ) = n − 1 and rank(c 2 (I n−1 −Ā n−1 )) = rank(L n−1 ) = n − 1, we obtain rank(L 2(n−1) ) = 2(n − 1).…”
Section: B Problem Formulationmentioning
confidence: 99%
“…Since rank(c 1 ) = n − 1 and rank(c 2 (I n−1 −Ā n−1 )) = rank(L n−1 ) = n − 1, we obtain rank(L 2(n−1) ) = 2(n − 1). By (16), it can be obtained rank(L) = 2(n − 1). Proceeding in a fashion similar to C1, it can be concluded that each closed-loop signal remains bounded, lim t→∞ (p i (t)−p j (t)) = 0, and L < p i (t) < U for all t ≥ 0, for all i, j = 1, .…”
Section: B Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations